Questioning as a Tool in Teaching - Ellen Tattelman; Arati Karnik; Alice Fornari (Association of American Medical Colleges, 2011)
Abstract The literature has shown that the targeted use of questioning can help evolve critical thinking skills in the learner. Thus, we developed this teaching handout to demonstrate the use of questioning to nurture the learner into higher levels of intellectual thinking. It is intended as a faculty development resource for community-based clinical faculty. This handout can be used to introduce the questioning strategies by first introducing the modified Bloom's taxonomy. The second page illustrates a concrete clinical example of how questions can be posed to learners to escalate to higher levels of thinking. This handout was developed to be posted or readily available in precepting areas as an easy reference tool. As a complement to the handout, we have created an interactive PowerPoint presentation geared towards residents in a resident-as-teacher session or toward faculty in a more detailed, interactive faculty development session. During these presentations, the participants observe a precepting demonstration that uses the modified Bloom's taxonomy hierarchy of questioning. They then actively take part in developing questions at all levels and role-play a typical clinic precepting case to practice what has been introduced. The format of nonconfrontational questioning presented here along Bloom's hierarchy of learning levels is designed to stimulate critical and creative thinking while the learners build confidence as they formulate answers.